Kajian Ekonomi Alih Fungsi Lahan di Kecamatan Pontianak Barat - Anggraeni, Vinsensia Puspita (Jurnal Pembangunan dan Pemerataan, 2019)
ABSTRACTThe phenomena of land convertion from agricultural land to non agricultural is currently happening, one of them is in West Pontianak, it can be seen from the data published by BPS Kota Pontianak that agricultural land in west in pontianak reduced 42ha from year 2012 to 2017.This study attempts to: know factors causing the change the function of the land and assess the impact of land convertion to household income of the land owner. Data analyzed in research is primary data obtained with the interview, the questionnaire, the literature study, documentation and observation.Then the data that have been acquired being processed and analyzed with the method of descriptive analysis .The result of this research is the factor that make the owner change the function of the land, were the internal household factors and external household factors. The impact of the land convertion to the ownerâ€™s household income is increasing the income of the households accordance with the expectation even though there are still household that have the stagnan income or decreasing income. Keyword : land convertion , household income , agriculture landReferensiAdisasmita, Rahardjo. 2008. Pengembangan Wilayah : Konsep Dan Teori. Yogyakarta: Penerbit Graha Ilmu.Afrida, 2003. Ekonomi Sumber Daya Manusia. Jakarta: Ghalia IndonesiaArsyad, Lincolin, 1999, Pengantar Perencanaan Dan Pembangunan Ekonomi Daerah, Yogyakarta: BPFE UGMBadan Pusat Statistik Kota Pontianak, 2013. Kecamatan Pontianak Barat Dalam Angka 2012. https://pontianakkota.bps.go.id/, diakses Minggu, 9 September 2018.Badan Pusat Statistik Kota Pontianak, 2015. Kota Pontianak Dalam Angka 2014. https://pontianakkota.bps.go.id/, diakses Jumat, 7 September 2018.Badan Pusat Statistik Kota Pontianak, 2015. Kota Pontianak Dalam Angka 2014. https://pontianakkota.bps.go.id/, diakses Jumat, 7 September 2018.Badan Pusat Statistik Kota Pontianak, 2015. Statistik Penggunaan Lahan Kota Pontianak 2014. https://pontianakkota.bps.go.id/, diakses Jumat, 7 September 2018.Badan Pusat Statistik Kota Pontianak, 2016. Kecamatan Pontianak Barat Dalam Angka 2015. https://pontianakkota.bps.go.id/, diakses Minggu, 9 September 2018.Badan Pusat Statistik Kota Pontianak, 2016. Statistik Penggunaan Lahan Kota Pontianak 2017. https://pontianakkota.bps.go.id/, diakses Jumat, 7 September 2018.Badan Pusat Statistik Kota Pontianak, 2017. Kota Pontianak Dalam Angka 2016. https://pontianakkota.bps.go.id/, diakses Jumat, 7 September 2018.Badan Pusat Statistik Kota Pontianak, 2017. Kota Pontianak Dalam Angka 2017. https://pontianakkota.bps.go.id/, diakses Jumat, 7 September 2018.Badan Pusat Statistik Kota Pontianak, 2017. Kecamatan Pontianak Barat Dalam Angka 2016. https://pontianakkota.bps.go.id/, diakses Minggu, 9 September 2018.Badan Pusat Statistik Kota Pontianak, 2017. Kecamatan Pontianak Barat Dalam Angka 2017. https://pontianakkota.bps.go.id/, diakses Minggu, 9 September 2018.Badan Pusat Statistik Kota Pontianak, 2018. Kecamatan Pontianak Barat Dalam Angka 2018. https://pontianakkota.bps.go.id/, diakses Minggu, 9 September 2018.Badan Pusat Statistik Kota Pontianak, 2018. Statistik Penggunaan Lahan Kota Pontianak 2017. https://pontianakkota.bps.go.id/, diakses Jumat, 7 September 2018.Black, J.A. 1981. Urban Transport Planning: Theory and Practice. London: Cromm HelmDinas Tenaga Kerja dan Transmigrasi Provinsi Kalimantan Barat, 2017. UMP / UMK di Provinsi Kalimantan Barat Tahun 2016-2018. https://Disnakertrans.kalbarprow.go.id/, diakses Sabtu, 29 Desember 2018.Dwi Andika, Kadek. dkk. 2017. Faktor-Faktor Yang Mempegaruhi Konversi Lahan Pertanian dan Hubungannya Terhadap Kesejahteraan Petani Subak Saih Di Kecamatan Kuta Utara, Kabupaten Badung. Jurnal Manajemen Agribisnis,Vol. 5, No.2, Oktober 2017.Fadjarajani, Siti, 2001, Pengaruh Alih Fungsi Lahan Pertanian Terhadap Kondisi Sosial Ekonomi Petani di Kecamatan Lembang Kabupaten Bandung : Implikasi Pada Perencanaan Pengembangan Wilayah, Thesis, Bandung: Pascasarjana ITBFajriany, Nur Isra. 2017. Analisis Faktor-Faktor Yang Mempengaruhi Alih Fungsi Lahan Pertanian di Kabupaten Pangkep. Skripsi. Universitas Negeri Alauddin : MakassarFatihudin, Didin, 2011, Pengaruh Investasi Swasta Dan Investasi Pemerintah Terhadap Pertumbuhan Ekonomi, Penyerapan Tenaga Kerja, Dan Tingkat Kesejahteraan Masyarakat Kabupaten/ Kota Di Provinsi Jawa Timur, Disertasi, Surabaya, Program Pascasarjana Universitas Airlangga.Irawan, B 2005. Konversi Lahan Sawah : Potensi Dampak, Pola Pemanfaatannya dan Faktor Determinan. Forum Penelitian Agro Ekonomi Volume 23, No. 1, Juni 2005. Pusat Analisis Sosial Ekonomi dan Kebijaan Pertanian : Bogor.Jhingan, ML. 2008.Ekonomi Pembangunan Dan Perencanaan. Jakarta: Raja Grafindo Persada.Koentjaraningrat. 1974. Kebudayaan Mentalitet dan Pembangunan. Jakarta: P.T Gramedia.Kurniasari, Merisa; Ariastita, Putu Gde. 2014. Faktor- Faktor yang Mempengaruhi Alih Fungsi Lahan Pertanian Sebagai Upaya Prediksi Perkembangan Lahan Pertanian di Kabupaten Lamongan.JURNAL TEKNIK POMITS Vol. 3, No. 2. 2014Kustiawan, Iwan. 1997. Permasalahan Konversi Lahan Pertanian dan Implikasinya Terhadap Penataan Ruang Wilayah (Studi Kasus Wilayah Pantura Jawa Barat). Jurnal PWK Volume 8 No. 1Nuryaman, Hendar. 2017. Tren Alih Fungsi Lahan Pertanian Ke Non Pertanian. Prosiding Seminar Nasional Hail Penelitian Agribisnis I FP UNIGAL. Ciamis: 1 April 2017. Hal. 577-583Rustiadi, Ernan; Saefulhakim, Sunsun; Panuju, Dyah R, 2011, Perencanaan Dan Pengembangan Wilayah, Jakarta: Crestpent Pres dan Yayasan Pustaka Obor IndonesiaSasono, Adi; Husein, Ali Sofyan. 1995. Ekonomi Politik Pengusaan Tanah. Jakarta : Pustaka Sinar Harapan.Schumacher, EF. 1973.Small is Beautiful. London: Blond and Briggs, Ltd.Sihaloho, Martua. 2004. Konversi Lahan Pertanian dan Perubahan Struktur Agraria. Tesis. Sekolah Pascasarjana. Institut Pertanian Bogor : BogorSugiyono. 2007. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung : AlfabetaSugiyono. 2016. Kuantitatif Kualitatif dan Kombinasi (Mixed Method). Bandung : AlfabetaTodaro, Michael P, and Smith, Stephen C, 2006, Pembangunan Ekonomi, Jakarta: ErlanggaUrep, Silvester Ansel. 2014. Pengaruh Produktivitas Usahatani Tanaman Pangan Dan Alih Fungsi Lahan Budidaya Tanaman Pangan Terhadap Pertumbuhan Ekonomi Dan Kesejahteraan Masyarakat Kabupaten/ Kota Di Provinsi Kalimantan Barat.Â  Disertasi. Program Doktor Universitas Airlangga : Surabaya.Utomo, Muhajir dkk. 1992. Pembangunan dan Pengendalian Alih Fungsi Lahan. Lampung: Universitas LampungYudhistira, Muhamad Dika. 2013. Analisis Dampak Alih Fungsi Lahan Pertanian Terhadap Ketahanan Pangan di Kabupaten Bekasi Jawa Barat (Studi Kasus Desa Sriamur Kecamatan Tambun Utara). Skripsi. Program Sarjana Institut Pertanian Bogor : Bogor